Implementasi Kepemimpinan Sebagai Peran Untuk Meningkatkan Kualitas Pada Lembaga Pendidikan Islam - Syafri Fadillah Marpaung; Yuni Syafriani; Suci Ramadhani; Amar Khairi Ahmad (Jurnal Ilmiah Wahana Pendidikan, 2023)
Leadership plays a key role in the direction, goals, and level of success in achieving the goals that have been set. Education is a form of organization where the level of success is largely determined by management and leadership factors. This fact shows how big the role of leadership in education is. Therefore, improvement of management and leadership systems in education is absolutely necessary. The existence of Islamic leadership also provides a balance between worldly concept leadership and the concept of ukhrowi to achieve essential goals more than just temporary organizational goals, demands a high commitment to Islamic principles and assigns a place of leadership not just a humanitarian task.